Same-sex behavior disclosure to health care providers associated with greater awareness of pre-exposure prophylaxis - Wangnan Cao; Xinyi You; Jinghua Li; Liping Peng; Jing Gu; Chun Hao; Fengsu Hou; Dannuo Wei; Yang Deng; Yuantao Hao; Phoenix Kit-han Mo (BMC, 2021)
Abstract Background This study aimed to determine whether the disclosure of same-sex behavior to health care providers (HCPs) is associated with higher rates of prior human immunodeficiency virus (HIV) testing experience and greater awareness of immediate antiretroviral therapy (ART), Undetectable = Untransmittable (U=U), and pre-exposure prophylaxis (PrEP) among men who have sex with men (MSM). Methods We conducted a cross-sectional survey among 689 adult males in Chengdu, China who self-reported having had anal intercourse with at least one man in the past 6 months. We measured same-sex behavior disclosure to three types of HCPs (hospital clinicians, community-based organization peer educators, and Center for Disease Control and Prevention public health specialists), and the awareness of immediate ART, U=U, and PrEP. Results Of the 689 enrolled participants, 31.4% had disclosed their same-sex behavior to some or all of the clinicians, 83.9% had done so to the peer educators, and 56.8% had done so to the public health specialists. Approximately four in five (82.1%) of the participants had ever been tested for HIV. The awareness rate was 84.8% for immediate ART, 20.2% for U=U, and 50.7% for PrEP. After controlling for significant background variables, same-sex behavior disclosure to clinicians was associated with greater awareness of PrEP (adjusted odds ratio [AOR] = 1.64; 95% confidence interval [CI]: 1.08-2.48), but similar findings were not reported regarding disclosure to peer educators or public health specialist. Same-sex behavior disclosure to any types of HCPs was not associated with HIV testing experience, and awareness of immediate ART or U=U. Conclusions The rates of same-sex behavior disclosure varied with different types of HCPs. Disclosure to clinicians was associated with greater awareness of PrEP, but not awareness of immediate ART or U=U.